The relationship between renal function indicators and preeclampsia in the second trimester of pregnancy: a retrospective study - Mingwei Li; Wei Liu; Xizhenzi Fan; Wenhui Song; Achou Su; Xue Zhang; Thomas Zheng; Tianxiao Yu (PeerJ)
Background To investigate the relationship between serum renal function indicators and preeclampsia (PE) in pregnant women at second trimester of pregnancy, determine the optimal critical values of the above indicators, and further identify the independent risk factors of PE. Methods We assessed the renal function indicators in second trimesters of 137 pregnant women with PE and 137 normal pregnant women who delivered at Shijiazhuang Fourth Hospital between January 2020 to December 2022. Paired t-tests, paired Mann-Whitney U tests, and Chi-square tests were used to evaluate differences of clinical data between the two groups. Receiver operating characteristic (ROC) curves was employed to establish the optimal critical values of the above indicators. A 1:1 matched case-control logistic regression analysis was conducted to identify the independent risk factors for PE. Results The levels of serum uric acid and the ratio of serum uric acid to serum creatinine were significantly higher in the PE group compared to the control (P < 0.001), while the serum creatinine levels were higher in control group (P = 0.002). The incidence of adverse maternal (P < 0.001) and neonatal outcomes (P < 0.001) in the PE group were higher than those in the control group. A ROC analysis based on the occurrence of PE showed that the levels of serum uric acid (P < 0.001), serum creatinine (P = 0.006) and the ratio of serum uric acid to serum creatinine (P < 0.001) were statistically significant. After adjusting for confounding factors, elevated serum uric acid (a OR = 1.012, 95% CI [1.005–1.019], P < 0.001) and an increased serum uric acid to serum creatinine ratio (a OR = 1.190, 95% CI [1.053–1.346], P = 0.005) were identified as independent risk factors for PE. There was no significant difference in renal function between maternal and newborn group in relation to the occurrence of adverse outcomes (P > 0.05 vs. all groups). Conclusions Through the analysis of renal function indicators in patients with PE in the second trimester of pregnancy and those in a normal control group, it is found that elevated serum uric acid and serum uric acid to serum creatinine ratio in PE individual may serve as indicative markers for the onset of PE. Targeting this subset of the population for monitoring and management during the second trimester could enhance the efficacy of medical interventions.